A novel potential measurement indicator with objective and quantitative effect for trigeminal neuralgia: fractional anisotropy in MR-DTI - Zhongshuai Ma; Xu Su; Xu Su; Zhengming Wang; Zhijia Wang; Min Cheng; Yu Tian; Chao Du (Frontiers in Neurology)
ObjectivesTo investigate the effect of diffusivity metrics of magnetic resonance diffusion tensor imaging (MR-DTI) in the assessment of treatment effects.MethodsMR-DTI examination for trigeminal neuralgia (TN) patients and the diffusivity metrics of the trigeminal ganglion (TG) were analyzed. Before and after the percutaneous stereotactic radiofrequency rhizotomy (PSR) operation, the treatment effect was assessed using pain scores and MR-DTI. The correlation between the diffusivity metrics of cranial nerve five (CNV) and visual analog scale (VAS) pain scores before and after treatment in TN patients was explored.ResultsIn PSR patients, the fractional anisotropy (FA) of the affected TG is a significantly lower than that of the unaffected side (p < 0.01). After PSR, the diffusivity metrics on the bilateral TGs are not significantly different (p > 0.05). Following PSR treatment, both of the diffusivity metrics (FA) in the lowest area of the CNV and the VAS scores of TN patients show changes. Furthermore, diffusivity metric (FA) on the lowest area of the CNV preoperative is significantly negatively correlated with the VAS scores (p < 0.05).ConclusionMR-DTI is capable of investigating the longitudinal changes of FA before and after radiofrequency treatment, and diffusivity metrics could be an independent reliable efficacy indicator for TN.SignificanceThe alteration of the diffusivity on TG may be correlated with the effect of radiofrequency treatment.